Lipid keratopathy in the dog - Crispin, Sheila M. (The University of Edinburgh, 1984)
Naturally occurring lipid keratopathy in the dog has been investigated using a variety of examination techniques. The same procedures have also been followed for a group of normal dogs matched to the clinical cases by age, sex and breed and for a third group of unmatched, normal, animals.

Investigations have included general clinical and ophthalmoscopic examination and detailed examination of the anterior segment, including tonometry, temperature measurement and fluorescein angiography. Laboratory examination has largely concentrated on serum lipid and lipoprotein analysis.

A number of microscopic methods have been applied to normal and diseased corneas. A comprehensive selection of histochemical techniques for identification of lipids have been used in conjunction with light, polarising, interference contrast and phase contrast microscopy. The physical properties of lipids have been explored using squash or imprint preparations, a heated microscope stage and polarised light (with a mica plate and a first order red gypsum accessory plate). A variety of other non-1ipid methods have also been used.

Ultrastructural studies complemented those of light microscopy, employing both scanning electron microscopy and transmission electron microscopy and utilising a limited number of ultrahistochemical staining techniques with the latter.

The results of this study indicate that lipid keratopathy may be associated with a variety of conditions involving the anterior segment and that abnormalities of the serum lipids and lipoproteins can often be demonstrated in affected animals. These findings are of significance for diseases of lipid metabolism in other species.